Caregiver’s burden and age are related determinants to quality of life in people with dementia - Resa Budi Deskianditya; Astuti Astuti; Yudiyanta Yudiyanta (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Dementia is a degenerative disease with poor prognosis. People with dementia will depend on their caregivers. Care for dementia patients aims to promote or preserve their quality of life. Identification of the factors that affect (determinants) the quality of life of people with dementia is required, and caregiver determinants are proven to play a role. The caregiver’s role could affect the frequency and variety of therapy. Long-term cognitive and physical disability in people with dementia further develops the caregiver’s burden. This study aimed to assess the determinants of caregivers which have a relation with the quality of life in people with dementia. This cross-sectional study involved subjects who are dementia patients at the Memory Clinic of Dr. Sardjito Hospital, Yogyakarta, Indonesia and fulfilled the inclusion criteria and did not meet the exclusion criteria. Subjects and caregivers were interviewed and helped to complete several questionnaires, including the DEMQOL, ZBI, and GDS. Analysis within variables was performed using Pearson, Mann-Whitney, and T-tests, followed by a multivariate linear regression analysis. As many as 76 people with dementia were included, with the majority having the diagnosis of vascular dementia (53.9%), and the average DEMQOL Career score was 80.58 + 17.62 and 81.82 + 20.80 for DEMQOL Proxy. Bivariate correlation analysis showed a significant correlation between the caregiver’s age, gender, family relation, burden (ZBI), and depression (GDS) with the quality of life people with dementia (p <0.05). In the multivariate analysis, caregiver’s age was related to the quality of life of people with dementia based on DEMQOL Career (B =0.270; p =0.001) and DEMQOL Proxy (B =0.271; p =0.001) and the caregiver burden was related to the quality of life of people with dementia based on DEMQOL Career (B =-0.629; p =0.000) and DEMQOL Proxy (B =-0.661; p =0.000). In conclusion, the determinants of caregiver that are significantly related to quality of life in people with dementia are caregiver’s burden and age.